Integrated transcriptomic and microbiomic analyses reveal mechanisms of Decapod iridescent virus 1 resistance in Macrobrachium rosenbergii - Hao, Jingwen; Jie, Yukun; Lu, Zhibin; Ye, Tiantian; Meng, Jilun; Liu, Cui; Yan, Junjun; Zheng, Yutong; Dong, Zaijie; Gu, Zhimin (Frontiers in Immunology, 2025)
Selective breeding for DIV1-resistant Macrobrachium rosenbergii is an effective strategy to mitigate aquaculture losses; however, the underlying resistance mechanisms remain poorly understood. In this study, approximately 2,300 prawns from 46 families were subjected to a DIV1 challenge test. Based on survival rate, viral load, histopathological observations, and viral gene detection in the transcriptome, one resistant family (R27-1) and one susceptible family (S2-2) were identified. Hepatopancreas transcriptomic (RNA-Seq) and gut microbiome analyses were conducted on samples at 0, 24, and 48 hours post-infection (hpi) from both families. A total of 144, 68, and 1,170 differentially expressed genes (DEGs) were identified at the respective timepoints. Three DEGs—including one corresponding to an uncharacterized lncRNA, an esterase E4-like protein, and a CUB-serine protease—were consistently differentially expressed at all timepoints. Transcriptomic data suggest that Melanogenesis, energy metabolism, and Steroid hormone biosynthesis pathways are associated with DIV1 resistance. Notable DEGs included hemocyanin, cytochrome P450, alkaline phosphatase-like, Friend leukemia integration 1 transcription factor-like, cytochrome P450 9e2-like, interferon regulatory factor 4-like, dual specificity protein phosphatase 10-like, trypsin II-P29-like, and cytochrome c oxidase subunit III. In addition, the potential probiotic Enterococcus casseliflavus (relative abundance: 0.51% vs 0.03%) was more abundant in the resistant family, whereas Lactococcus garvieae (RA: 20.18% vs 70%) was enriched in the susceptible one. These findings highlight the combined contribution of host transcriptomic responses and gut microbial communities to DIV1 resistance. To the best of our knowledge, this is the first study to integrate transcriptomic and microbiomic analyses for investigating DIV1 resistance in M. rosenbergii. These findings provide novel insights into the host–pathogen interaction and offer valuable targets for selective breeding of DIV1-resistant M. rosenbergii in aquaculture.